Pengaruh Kompensasi Terhadap Kinerja Karyawan Melalui Prestasi Kerja Karyawan pada PT. Nippon Paint Kediri - Saputra, Beny Mahyudi (STIE Malangkucecwara, 2019)
The objectives of this study are: 1). Knowing the effect of compensation on employee performance directly. 2). Knowing the effect of compensation on employee performance. 3). Knowing the effect of work performance on employee performance. 4). Knowing the effect of compensation on employee performance through work performance. The population is defined as